Marketing of Management: Share Market, Potential Market, Competitor Business and Promotion (Literature Review) - Nur Mastuti, Dian; Eko Widodo, Rintis; Wijanarko, Bambang; Purwoko, Harry; Suhendra, Agus (International Journal of Advanced Multidisciplinary, 2024)
Literature review research on marketing management: market share, potential market, competitor business, and promotion is a scientific literature article in the scope of marketing management science. The purpose of this literature research is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. The data used in this descriptive qualitative approach comes from previous research that is relevant to this study and is sourced from academic online media such as the Scopus Emerald Journal, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Market Share influences Marketing Management; 2) Potential Market influences Marketing Management; 3) Competitor Business influences Marketing Management; and 4) Promotion influences Marketing Management.